2020
DOI: 10.1186/s12884-020-03297-w
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness complication readiness and determinants among pregnant women: a community-based survey from Ethiopia

Abstract: Background Maternal death related to obstetric complications remains a great challenge in developing countries. Since these complications are not consistently predictable, it is important to plan different preventive approaches to overcome them when. As the information on birth preparedness, complication readiness, and predictors were limited in the study area, we conducted this study. Methods A Cross-sectional study involving 396 pregnant women was conducted from 1st April to 1st May 2018. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In contrast, similar findings were seen in Rwanda (22.3%) and Ethiopia (22.2%) [29,30]. Such findings were also found in a local study conducted in Pakistan (23.6%) [31].…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, similar findings were seen in Rwanda (22.3%) and Ethiopia (22.2%) [29,30]. Such findings were also found in a local study conducted in Pakistan (23.6%) [31].…”
Section: Discussionsupporting
confidence: 84%
“…These might have been influenced by the unique developmental stage of the city area of Tanzania, which recently became a middle-income country. Although ANC more than four times [ 21 – 23 ], first ANC within the first trimester [ 22 ], income [ 24 ], and age [ 24 26 ].showed significant relationships with BPR in previous studies, they were not found to be associated in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Participants belonging to age group of 28-32 years and Occupation of Spouse were the independent predictor for birth preparedness in this study which is similar with the study done by Ananche et al age 18-19 years (AOR = 0.18; 95% CI (0.04,0.94)). 24 and Akshaya et al age >26 years (adj OR = 2.97; 95%CI: 1.15-7.7). 3 In Developing Countries, knowledge related to pregnancy and preparedness is passed on across generations or gained through experience.…”
Section: Discussionmentioning
confidence: 93%